Septoria Leaf Spot of Tomatoes: Historical Insights, Present Challenges, and Future Prospects - Anju Pandey; Rajan Paudel; Tika B. Adhikari; Dilip R. Panthee; Frank J. Louws (Horticulturae)
Septoria leaf spot (SLS), caused by the hemibiotrophic fungus Septoria lycopersici, poses a significant threat to tomato production systems. While fungicides can effectively reduce disease epidemics, planting resistant cultivars remains the most efficient and economical control method. Conventional screening and breeding have identified new sources of resistance to S. lycopersici among wild relatives. However, gaps exist in the literature concerning tomato—S. lycopersici interactions, such as plant defense mechanisms, fungal pathogenicity mechanisms, and interaction dynamics that can inform the development of durable resistance through additional research. To further enhance host resistance to S. lycopersici, molecular methods such as marker-assisted breeding, gene editing, genomic selection, and transgenic approaches can be employed. Moreover, the durability of resistance and efficacy of disease management can be optimized within an integrated pest management (IPM) framework that advances diverse tactics to suppress diseases and improve plant productivity. This review highlights the current understanding of pathogen biology, host genetic solutions, and novel strategies to combat the SLS problem and suggests directions for future research.